Labor markets, regional socioeconomic disparities and poverty in Costa Rica, 2010-2017 - Izquierdo Vázquez, Carlos (2022)
With the National Household Survey (2010-2017) it is determined that there were significant gaps between the socioeconomic regions of Costa Rica. The Central Region was mostly urban and concentrated the most dynamic activities of the “new economy”. The other regions presented a higher proportion of poor population, mainly employed in agricultural work. The poor were characterized by having incomplete basic education, low income, participation in low-skilled jobs and higher levels of labor informality and non-compliance with labor rights. It was more difficult for the population in extreme poverty to get out of their condition, since their income (considerably lower than that of the rest of the poor) hardly increased, despite the implementation of some targeted social policies.